Delimitating cryptic species in the Gracilaria domingensis complex (Gracilariaceae, Rhodophyta) using molecular and morphological data. Issue 6 (15th September 2016) - Lyra, Goia de M.; Gurgel, C. Frederico D.; Costa, Emmanuelle da S.; de Jesus, Priscila B.; Oliveira, Mariana C.; Oliveira, Eurico C.; Davis, Charles C.; Nunes, José Marcos de Castro
Abstract : Species in the genus Gracilaria that display conspicuously flattened vegetative morphologies are a taxonomically challenging group of marine benthic red algae. This is a result of their species richness, morphological similarity, and broad phenotypic plasticity. Within this group, the Gracilaria domingensis complex is one of the most common, conspicuous, and morphologically variable species along the tropical western Atlantic Ocean. Previous research has identified that members of this complex belong to two distantly related clades. However, despite this increased phylogentic resolution, species delimitations within each of these clades remain unclear. Our study assessed the species diversity within this difficult complex using morphological and molecular data from three genetic markers ( cox 1, UPA, and rbc L). We additionally applied six single‐marker species delimitation methods (SDM: ABGD, GMYCs, GMYCm, SPN, bPTP, and PTP) to rbc L, which were largely in agreement regarding species delimitation. These results, combined with our analysis of morphology, indicate that the G. domingensis complex includes seven distinct species, each of which are not all most closely related: G. cervicornis ; a ressurected G. ferox ; G. apiculata subsp. apiculata ; a new species, Gracilaria baiana sp. nov.; G. intermedia subsp. intermedia ; G. venezuelensis ; and G. domingensis sensu stricto, which includes the later heterotypic synonym, G. yoneshigueana . Our study demonstrates the value of multipronged strategies, including the use of both molecular and morphological approaches, to decipher cryptic species of red algae.